2019
DOI: 10.3390/ma12152348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dislocation Density Evolution on Mechanical Behavior of OFHC Copper during High-Speed Machining

Abstract: This paper aims at investigating the change in material behavior induced by microstructure evolution during high-speed machining processes. Recently, high-speed machining has attracted quite a lot of interest from researchers due to its high efficiency and surface quality in machining large-scale components. However, the material behavior could change significantly at high-cutting speeds compared to the conventional cutting conditions, including their microstructure and t mechanical response. This is due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The complete reverse (opposite) process is the modeling of the material separation. In this case, the process should be designed in such a way that the Huber–Mises reduced stress should exceed the allowable stress that appears in the direct cutting zone [5,6,7,8,9,10,11]. Otherwise, the material being removed would not be separated.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete reverse (opposite) process is the modeling of the material separation. In this case, the process should be designed in such a way that the Huber–Mises reduced stress should exceed the allowable stress that appears in the direct cutting zone [5,6,7,8,9,10,11]. Otherwise, the material being removed would not be separated.…”
Section: State Of the Artmentioning
confidence: 99%
“…Nowadays, the works concerning the numerical modelling of machining processes using FEM (the finite element method) are very popular. Many literature positions describe numerical or experimental investigations of machining processes, such as turning [5], milling [6,7,8], boring [9,10], grinding [11], etc. Much less attention is given to covering mechanical cutting on guillotines [12,13,14,15,16,17,18].…”
Section: State Of the Artmentioning
confidence: 99%
“…With the increase in the cutting speed, feed rate, and radial cutting depth, the grain size of the machined surface changes slightly and gradually returns to its initial size. Liu et al [17] simulated the cutting process of OFHC copper using the DDB model and concluded from the experiment and simulation results that the fluctuation of a cutting force at high cutting speed was caused by the evolution and distribution of the dislocation density. The dislocation density on the machined surface increased with the increase in cutting speed, while it decreased in the chips.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations of the behaviour of materials require constitutive equations that account for properties such as inelastic deformation (flow stress) and damage evolution as a function of variables such as strain, strain rate and temperature. Because of simplicity and the wide availability of required coefficients and constant parameters, numerical simulations of dynamic properties of materials such as alloys of titanium, aluminium, copper and steel, are normally based on the Johnson–Cook (J–C) material model [ 32 , 33 , 34 , 35 ]. This model is in-built in the commercial finite element analysis (FEA) software ABAQUS/Explicit for simulating high-strain-rate deformation of materials including the simulation of adiabatic transients [ 36 ].…”
Section: Introductionmentioning
confidence: 99%